Determinants of entrepreneurial success: A comparative analysis of farm and non-farm sectors - F, KOBBA; NAIN, M S; SINGH, RASHMI; MISHRA, J R; A, SHITU G (The Indian Journal of Agricultural Sciences, 2021)
Entrepreneurship development has become the centre of many emerging economies as it is believed that entrepreneurship contributes significantly to economic growth. Quite a good number of researches have been done on factors that determine entrepreneurial success. However, the farm sector has been neglected for far too long. Present study, looked at a comparative analysis of farm and non-farm sectors in Krishi Vigyan Kendra (KVK) and Rural Development and Self Employment Training Institute (RUDSETI) to determine the factors that predict entrepreneurial success. A semi-structured interview schedule was used in 2019 to solicit information on sociodemographic and entrepreneurial characteristics from respondents. Entrepreneurs were categorized into successful and non-successful based on turnover, income and number of employees. Discriminant function analysis was used to predict the determinants of success in both farm and non-farm sectors. Results revealed that in the farm sector, four determinants of entrepreneurial success were family size, land size, turnover and annual income whereas in the non-farm sectors five determinants of entrepreneurial success were long term involvement, initiative, number of employees, entrepreneurial experience and annual income. Chi-square showed no significant difference in the success rate between farm and non-farm entrepreneurs. Policies to create the enabling environment to address access to market, market information and credit should be put in place for higher success rate of potential entrepreneurs.